2017
DOI: 10.1016/j.sleep.2017.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and slow-wave activity in depressed adolescent boys: a preliminary study

Abstract: Depression in adolescent boys is characterized by more evenly distributed SWA through the night as compared to healthy subjects, and we showed for the first time that this pattern of SWA distribution is associated with severity of depressive symptoms. These findings suggest that homeostatic regulation of sleep may be impaired in adolescent depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…It is postulated that the decrease in SWA during the course of sleep is associated with reduced synaptic strength and is thus related to memory consolidation [51]. Our previous results on the same sample of adolescents indicated that this SWA dissipation that occurs normally during healthy sleep is affected by depression and related sleep disturbances [23]. The results of the current study further propose a link between SWA dissipation and changes in methylation of the Protein Phosphatase 2 regulatory subunit B'gamma (PPP2RC5).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…It is postulated that the decrease in SWA during the course of sleep is associated with reduced synaptic strength and is thus related to memory consolidation [51]. Our previous results on the same sample of adolescents indicated that this SWA dissipation that occurs normally during healthy sleep is affected by depression and related sleep disturbances [23]. The results of the current study further propose a link between SWA dissipation and changes in methylation of the Protein Phosphatase 2 regulatory subunit B'gamma (PPP2RC5).…”
Section: Discussionsupporting
confidence: 64%
“…Different sleep disturbances can therefore affect LTP and LTD differently [56,66]. Since in our sample there was no marked difference in REM sleep between cases and controls [23], it is plausible that there were no differences in LTP genetic pathways either.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…EEG signals can be analyzed by linear and non-linear dynamic analyses. Linear analysis such as power spectrum is commonly used to extract the features of sleep EEG signals [13,26,40,44]. Spectral characteristic parameters can reflect the energy information transported by each frequency band.…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy might be explained mainly by the considerably longer follow-up time in our current study, as well as the differing methods for assessing sleep abnormalities (objective sleep EEG vs. subjective reports). Polysomnographic studies in MDD point overall towards alterations in sleep continuity, sleep depth, and REM sleep pressure [30,31], the findings being less consistent and less severe among children and adolescents than among adults [30][31][32]. In turn, subjective sleep complaints among depressed adolescents include insomnia or hypersomnia, experiences of insufficient sleep quality, and daytime sleepiness [29,31].…”
Section: Discussionmentioning
confidence: 99%